Preparation and evaluation of zinc oxide (ZnO) metal nanoparticles carriers for azilsartan - Abdulbaqi, Mustafa R; Kassab, Hanan J; Abdulelah, Furqan M (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
The present study involves the utilization of metal oxide nanoparticles, zinc oxide (ZnO), as a drug delivery module for the antihypertensive drug, azilsartan, as a tool of particle size reduction. According to biopharmaceutical classification system (BCS), azilsartan belong to class II with low solubility and high permeability. ZnO nanoparticles was synthesized using chemical precipitation method, and then three formulations (FI, FII, and FIII) were prepared using variable azilsartan medoxomil / ZnO nanoparticles molar ratios. Formula III, with 2:1 drug / nanocarrier molar ratio, was found to contain the higher percent of loaded drug and therefore was selected for further studies as the most optimum formulation. The release rate of azilsartan medoxomil from ZnO complex showed significant (p ≤ 0.05) enhancement than pure drug with complete liberation after 60 minutes. High values of percent yield, entrapment efficiency and drug loading of FIII indicate successful loading and efficient FIII formulation. The X- ray diffractogram and DSC thermogram of FIII reveal stable formulation with decreased crystallinity of surface loaded drug. AFM images reveal particle size reduction as noted by the increased surface area ratio of FIII (114) in comparison to azilsartan medoxomil (2.9) at the same image size. FTIR indicate stable FIII formulation with no chemical interaction. As a conclusion, azilsartan medoxomil was loaded successfully on synthesized metal ZnO nanoparticles with optimized properties in term of dissolution rate and crystallinity.